2018
DOI: 10.1111/jog.13748
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial and angular pregnancies: Case reports and differential diagnosis

Abstract: Interstitial and angular pregnancies are rare and have high rates of morbidity and mortality. These terms continue to create confusion and are frequently misused. The standardization of terminology and differentiation of cases is necessary to distinguish between different outcomes. This article aims to report one case of angular and another case of interstitial pregnancies and to discuss clinical and radiological characteristics, prognosis and treatment. These pathologies continue to be confused with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In angular pregnancy, the gestational sac remains in the uterine cavity, but it is close to the cornua of uterus and its enlargement causes an overall outward and upward displacement of the round ligament, whereas in interstitial pregnancy, the enlargement of the gestational sac has no effect on the position of the round ligament, and it only causes a local enlargement of the segment of the fallopian tube that travels inside the uterus 7 . In recent years, cases of complications due to angular pregnancy have occasionally been reported, mostly of uterine rupture 10–12 . The results of the latest and largest prospective study of angular pregnancy to date, conducted by Bollig et al., showed that 80% of angular pregnancy cases resulted in a live birth when monitored closely throughout pregnancy, breaking the previously held association between angular pregnancy and adverse pregnancy events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In angular pregnancy, the gestational sac remains in the uterine cavity, but it is close to the cornua of uterus and its enlargement causes an overall outward and upward displacement of the round ligament, whereas in interstitial pregnancy, the enlargement of the gestational sac has no effect on the position of the round ligament, and it only causes a local enlargement of the segment of the fallopian tube that travels inside the uterus 7 . In recent years, cases of complications due to angular pregnancy have occasionally been reported, mostly of uterine rupture 10–12 . The results of the latest and largest prospective study of angular pregnancy to date, conducted by Bollig et al., showed that 80% of angular pregnancy cases resulted in a live birth when monitored closely throughout pregnancy, breaking the previously held association between angular pregnancy and adverse pregnancy events.…”
Section: Discussionmentioning
confidence: 99%
“…7 In recent years, cases of complications due to angular pregnancy have occasionally been reported, mostly of uterine rupture. [10][11][12] The results of the latest and largest prospective study of angular pregnancy to date, conducted by Bollig et al, showed that 80% of angular pregnancy cases resulted in a live birth when monitored closely throughout pregnancy, breaking the previously held association between angular pregnancy and adverse pregnancy events. In addition, their study also established three clear criteria for the diagnosis of angular pregnancy by 3D ultrasound which was the surrounding endometrium sign, myometrium mantle thickness less than 5 mm and the absence of the interstitial tubal line sign.…”
Section: Discussionmentioning
confidence: 99%
“…An interstitial pregnancy is an ectopic pregnancy implanted in the interstitial part of the fallopian tube and close to the uterine musculature. Interstitial pregnancies implant lateral to the round ligament and are approximately 1-2 cm within the intra-myometrial region of the tube, with the gestational sac surrounded by less than 5 mm of the myometrium in all scanning planes, a chorionic sac separate (> 1 cm) from the lateral edge of the uterine cavity, and the presence of an interstitial line sign [ 6 , 16 , 17 , 18 ]. In the literature, the sensitivity and specificity of the sonographic “interstitial line sign” varies from 80% to 100% [ 16 , 11 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angular pregnancy is the third type of pregnancy in the normal cornual region of the uterus and is a differential diagnosis of interstitial or true cornual pregnancy. Anatomically, angular pregnancy implants medial to the round ligament, at the lateral angle of the endometrial/uterine cavity, and just medial to the uterotubal junction [17] . Angular pregnancy can progress to term because it is technically inside the uterine/endometrial cavity [ 5 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation